2019
DOI: 10.3390/pr7100661
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Process Methodology for Multi-Frequency Marine Controlled-Source Electromagnetic Profile Estimation in Isotropic Medium

Abstract: The marine controlled-source electromagnetic (CSEM) technique is an application of electromagnetic (EM) waves to image the electrical resistivity of the subsurface underneath the seabed. The modeling of marine CSEM is a crucial and time-consuming task due to the complexity of its mathematical equations. Hence, high computational cost is incurred to solve the linear systems, especially for high-dimensional models. Addressing these problems, we propose Gaussian process (GP) calibrated with computer experiment ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(61 reference statements)
0
2
0
2
Order By: Relevance
“…Sonuçları oluşturan temel işlevin, tamamen bir ortalama işlev, m(x) ve bir kovaryans işlevi, k(x,x') tarafından belirtilen stokastik bir süreç olan bir Gauss Süreci olduğu varsayımına dayanır. Gauss Sürecinin ortalama işlevi, girdi değişkenlerini çıktı değişkenlerine eşleyen herhangi bir işlev olabilirken kovaryans işlevi, işlevin düzgünlüğünü ve benzerliğini kodlar [49], [50].…”
Section: Gauss Süreç Regresyonu (Gsr)unclassified
See 1 more Smart Citation
“…Sonuçları oluşturan temel işlevin, tamamen bir ortalama işlev, m(x) ve bir kovaryans işlevi, k(x,x') tarafından belirtilen stokastik bir süreç olan bir Gauss Süreci olduğu varsayımına dayanır. Gauss Sürecinin ortalama işlevi, girdi değişkenlerini çıktı değişkenlerine eşleyen herhangi bir işlev olabilirken kovaryans işlevi, işlevin düzgünlüğünü ve benzerliğini kodlar [49], [50].…”
Section: Gauss Süreç Regresyonu (Gsr)unclassified
“…burada X girdi değişkenlerinin matrisidir, Ɵ hiperparametrelerin bir vektörüdür, K, k(xi,xj) öğelerini içeren kovaryans matrisidir, σ 2 gürültü varyansıdır [50], [51]. GSR'nin amacı ise aşağıda verilen f(x) fonksiyonunu bulmaktır ki; bu fonksiyon y'nin x üzerindeki dağılımıdır [51]:…”
Section: Gauss Süreç Regresyonu (Gsr)unclassified
“…GP is a probabilistic and nonparametric method which capable of fitting functional forms reliant on the domain observations. According to Reference [25], this stochastic approach has a property that differs from most of the other black-box identification approaches. It searches for the correlations among the known knowledge rather than approximating the model by trying to fit the basis function parameters.…”
Section: Stochastic Process-gaussian Processmentioning
confidence: 99%
“…Studies related to the commercial SBL application can be found in [1][2][3][4][5][6][7][8][9]. Figure 1 is adopted from [10] to depict the illustration of the SBL application in the offshore environment. Numerical modeling is a crucial task in geophysics problems since it provides prior knowledge and information of the potential reservoirs.…”
Section: Introductionmentioning
confidence: 99%